A composite fluorine-containing dissolving agent for determination of sulfur content in fluorite, a preparation method and application thereof

CN122983289APending Publication Date: 2026-10-27HARBIN WELL WELDING CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611004241.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-27

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a composite fluorine-fixing fluxing agent for determination of sulfur content in fluorite, a preparation method and application thereof, and belongs to the technical field of analytical chemistry. The application uses CaO, La2O3 and CuO as the composite fluorine-fixing fluxing agent, and realizes hierarchical fluorine fixation and dynamic fluxing by using the synergistic effect of the three, effectively solves the technical problems that a combustion tube is prone to corrosion and sulfur is not completely released during determination of a fluorine-containing sample, remarkably prolongs the service life of the combustion tube, and improves the accuracy and reproducibility of analysis results.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composite solid fluorine co-solvent for determining the sulfur content in fluorite, its preparation method, and its application, belonging to the field of analytical chemistry technology. Background Technology

[0002] Fluorite, whose main component is CaF2, is an important non-metallic mineral raw material in industry, and its sulfur content is a key indicator for measuring ore quality. High-frequency infrared carbon-sulfur analyzers are the mainstream equipment for determining carbon and sulfur elements in minerals. Their principle involves high-frequency induction heating and combustion of the sample under oxygen-rich conditions, converting carbon into CO2 and sulfur into SO2, which are then detected.

[0003] However, fluorite samples release a large amount of fluorine-containing gases during high-frequency combustion, mainly HF and SiF4. These corrosive gases cause severe chemical corrosion to the inner wall of the quartz combustion tube of the analyzer, leading to atomization and cracking on the surface of the combustion tube, significantly shortening its service life. In addition, fluorides can interfere with the release and detection of sulfur, resulting in lower results or poor repeatability.

[0004] To address the aforementioned issues, existing technologies often employ the addition of fluorine-fixing agents. However, traditional fluorine-fixing agents, such as calcium carbonate and magnesium oxide alone, have limited fluorine-fixing efficiency and do not adequately consider fluxing effects, combustion temperature, and sample melt flowability, making it difficult to simultaneously meet the multiple requirements of complete combustion, accurate measurement, and instrument protection for fluorite samples. Therefore, it is essential to provide a composite fluorine-fixing flux for determining sulfur content in fluorite to achieve efficient fluorine fixation, reduce fluorine corrosion, improve combustion conditions, enhance the accuracy and reproducibility of sulfur measurement results, and significantly extend the life of the combustion tube. Summary of the Invention

[0005] To address the problems of corrosion of the combustion tube and inaccurate measurement results in sulfur determination of fluorite samples, this invention provides a composite solid fluorine co-solvent for the determination of sulfur content in fluorite, its preparation method, and its application.

[0006] The technical solution of the present invention: One objective of this invention is to provide a composite solid fluorine co-solvent for determining the sulfur content in fluorite, wherein the composite solid fluorine co-solvent comprises, by weight: 50%–80% tungsten particles, 15%–30% tin particles, and 10%–25% composite solid fluorine oxidant; The composite solid fluorine oxidant comprises calcium carbonate, lanthanum oxide, and copper oxide in a weight ratio of (4.5–5.5):(2.5–3.5):(1.5–2.5).

[0007] Further restrictions are imposed, with the particle size of calcium carbonate, lanthanum oxide, and copper oxide not exceeding 200 mesh.

[0008] Further specified, the composition is 60%–70% tungsten particles, 16%–25% tin particles, and 12%–22% composite solid fluorine oxidant.

[0009] Further specified, the weight ratio of calcium carbonate, lanthanum oxide and copper oxide is (4.8-5.2):(2.8-3.2):(1.8-2.2).

[0010] Further specified, the tungsten particles have a particle size of 0.4mm to 0.8mm and a purity of ≥99.9%; the tin particles have a particle size of 0.2mm to 0.5mm and a purity of ≥99.5%.

[0011] The second objective of this invention is to provide a method for preparing the composite solid fluorine co-solvent for determining the sulfur content in fluorite. The method is as follows: calcium carbonate, lanthanum oxide and copper oxide are mixed to obtain a composite solid fluorine oxidant powder, then tungsten particles and tin particles are added, and after mechanical mixing, the mixture is dried at 105-120°C for 2-4 hours, cooled and sealed for later use.

[0012] The third objective of this invention is to provide a method for determining the sulfur content in fluorite. The method involves placing the fluorite sample to be tested in a ceramic crucible, adding the aforementioned composite solid fluorine co-solvent used for determining the sulfur content in fluorite to cover the fluorite sample, turning on a high-frequency infrared carbon-sulfur analyzer to perform combustion determination, and calculating the sulfur content in the fluorite.

[0013] Further, the mass of the composite solid fluorine co-solvent is 2 to 5 times the mass of the fluorite sample to be tested.

[0014] Furthermore, the mass of the composite solid fluorine co-solvent is 3 to 4 times the mass of the fluorite sample to be tested.

[0015] To further limit this, the flux blank value is measured in advance before the test, and the high-frequency infrared carbon-sulfur analyzer automatically deducts the pre-measured flux blank value during the test.

[0016] Beneficial effects: This invention utilizes CaO, La2O3, and CuO as a composite solid-fluorine flux, leveraging their synergistic effect to achieve graded solid-fluorine fixation and dynamic fluxing. This effectively solves the technical challenges of easy corrosion of the combustion tube and incomplete sulfur release during the analysis of fluorine-containing samples, significantly extending the combustion tube's lifespan and improving the accuracy and reproducibility of analytical results. Compared with existing technologies, this invention also has at least the following advantages: (1) This invention utilizes the decomposition of calcium carbonate into CaO at high temperature, which reacts with fluorides to generate stable CaF2; lanthanum oxide (La2O3) reacts with fluorine to generate high-melting-point, low-volatility LaOF or LaF3, further enhancing the fluorine fixation effect; copper oxide (CuO) acts as a fluxing component, reducing melt viscosity and promoting the fluorine fixation reaction kinetics. The synergistic effect of these three components firmly fixes fluorine in the slag, resulting in almost no corrosive fluorides in the exhaust gas and significantly extending the life of the quartz combustion tube.

[0017] (2) This invention utilizes the high magnetic permeability of tungsten particles to effectively improve the efficiency of induction heating, enabling the sample to be heated rapidly to the temperature required for complete combustion; tin particles have a low melting point and melt first to form a liquid phase during combustion, which encapsulates the sample and promotes oxygen penetration, which is conducive to the full oxidation of sulfides; the copper oxide in the composite solid fluorine oxidant provides an oxygen-rich environment to promote the complete oxidation of sulfur, ensuring complete sulfur release and improving the accuracy and reproducibility of the analytical results.

[0018] (3) The present invention eliminates the interference of trace sulfur that may be introduced by the flux itself through strict drying treatment and the instrument automatically deducting the pre-measured blank value of flux during the measurement process, which is particularly suitable for the accurate analysis of trace sulfur.

[0019] (4) The flux provided by the present invention is a solid powder, which is simple to prepare and does not require additional additives. It can be directly measured after weighing and mixing once. It is suitable for various models of high-frequency infrared carbon and sulfur analyzers and has the advantages of simple operation and strong universality. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0021] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0022] The high-frequency infrared carbon-sulfur analyzer used in the following examples is a LECO CS744 carbon-sulfur analyzer from the United States, and the quartz combustion tube is an original part; the fluorite sample is chemical analysis sample QD19-273 fluorite 16# produced by Jinan Quandong Standard Material Research Institute, and its sulfur content standard value is 0.016%.

[0023] Example 1 The composite solid fluorine flux provided in this embodiment includes: 32.25g of tungsten granules, 9.7g of tin granules, and 8.05g of composite solid fluorine oxidant; wherein the composite solid fluorine oxidant includes 4.025g of calcium carbonate, 2.415g of lanthanum oxide, and 1.61g of copper oxide.

[0024] The preparation method of the composite solid fluorine flux provided in this embodiment includes: Step 1: Weigh calcium carbonate, lanthanum oxide and copper oxide according to the proportion, put them in a grinding device and mix and grind for 4 minutes, then pass them through a 200-mesh sieve to obtain a composite solid fluoride oxidant powder with a particle size ≤200 mesh. Step 2: Weigh out tungsten granules, tin granules and the composite solid fluorine oxidant prepared in step 1 according to the proportion, and put them into a mixer for mechanical mixing for 30 minutes; Step 3: Dry the mixed material at 105℃ for 4 hours, cool it, seal it, and set it aside for later use.

[0025] The method for determining the sulfur content in fluorite provided in this embodiment includes: (1) Weigh 0.2g of fluorite sample and place it in a ceramic crucible. Cover the fluorite sample with 0.6g of composite solid fluorine flux and place the ceramic crucible in a quartz combustion tube. (2) Turn on the high-frequency infrared carbon-sulfur analyzer to perform combustion determination. During the determination process, the instrument will automatically deduct the pre-measured flux blank value. (3) Repeat the chemical analysis sample 6 times and read the detection data of sulfur content of fluorite sample. The results are shown in Table 1.

[0026] Table 1 After completing six tests using the above flux, the inner wall of the quartz combustion tube was observed and found to remain transparent and smooth, with no obvious signs of atomization or corrosion.

[0027] Example 2 The difference between this embodiment and Embodiment 1 is that the composite solid fluorine flux provided in this embodiment includes: 37.5g of tungsten granules, 7.5g of tin granules, and 5g of composite solid fluorine oxidant; wherein the composite solid fluorine oxidant includes 2.647g of calcium carbonate, 1.47g of lanthanum oxide, and 0.88g of copper oxide; the remaining process steps and parameter settings are the same as in Embodiment 1.

[0028] The detection data of sulfur content in the fluorite sample in this embodiment are shown in Table 2.

[0029] Table 2 After completing six tests using the above flux, the inner wall of the quartz combustion tube was observed to have a very slight white haze-like deposit, but this did not affect light transmission or use.

[0030] Example 3 The difference between this embodiment and Embodiment 1 is that the composite solid fluorine flux provided in this embodiment includes: 30g of tungsten granules, 7.5g of tin granules, and 12.5g of composite solid fluorine oxidant; wherein the composite solid fluorine oxidant includes 5.978g of calcium carbonate, 3.804g of lanthanum oxide, and 2.717g of copper oxide; the remaining process steps and parameter settings are the same as in Embodiment 1.

[0031] The detection data of sulfur content in the fluorite sample in this embodiment are shown in Table 3.

[0032] Table 3 After completing six tests using the above flux, the inner wall of the quartz combustion tube was observed to have a small amount of deposits, but the overall condition was good.

[0033] Comparative Example 1 The difference between this comparative example and Example 1 is that the amount of composite solid fluorine oxidant used is 0g; the remaining process steps and parameter settings are the same as in Example 1.

[0034] The sulfur content detection data of the comparative fluorite sample (three tests were completed consecutively using the above flux) are shown in Table 4. After completing three tests consecutively using the above flux, the inner wall of the quartz combustion tube was observed. Due to the complete lack of solid fluorine components, fluorides severely corroded the quartz combustion tube, causing serious interference to the detection system.

[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that: 20.0g of tungsten granules, 10.0g of tin granules, and 20.0g of composite solid fluorine oxidant; wherein the composite solid fluorine oxidant includes 10.0g of calcium carbonate, 6.0g of lanthanum oxide, and 4.0g of copper oxide; the remaining process steps and parameter settings are the same as in Example 1.

[0036] The sulfur content detection data of the comparative example fluorite sample (three tests were completed consecutively using the above flux) are shown in Table 4. Analysis of Table 4 shows that due to the excessively low tungsten particle content in the high-permeability medium and the excessive amount of high-melting-point oxidant, the high-frequency induction heating efficiency was severely insufficient, the combustion temperature could not reach the temperature required for complete combustion of the sample, and the release was incomplete.

[0037] Comparative Example 3 The difference between this comparative example and Example 1 is that: 32.25g of tungsten granules, 9.7g of tin granules, and 8.05g of composite solid fluorine oxidant; wherein the composite solid fluorine oxidant includes 6.038g of calcium carbonate, 0.805g of lanthanum oxide, and 1.207g of copper oxide; the remaining process steps and parameter settings are the same as in Example 1.

[0038] The sulfur content detection data of the comparative fluorite sample (three tests were performed consecutively using the above flux) are shown in Table 4. Analysis of Table 4 shows that due to a severe deficiency of lanthanum oxide, the fluorine released during the medium-to-high temperature stages could not be effectively fixed, leading to corrosion of the quartz tube.

[0039] Comparative Example 4 The difference between this comparative example and Example 1 is that: 32.25g of tungsten granules, 9.7g of tin granules, and 8.05g of composite solid fluorine oxidant; wherein the composite solid fluorine oxidant includes 4.830g of calcium carbonate, 2.818g of lanthanum oxide, and 0.402g of copper oxide; the remaining process steps and parameter settings are the same as in Example 1.

[0040] The sulfur content detection data of the comparative fluorite sample (three tests were completed consecutively using the above flux) are shown in Table 4. Analysis of Table 4 shows that due to a severe deficiency of copper oxide, which plays a role in in-situ oxygen supply and reducing melt viscosity, the melt flowability of the reaction system was extremely poor, hindering the release of sulfur.

[0041] Table 4 As can be seen from the above examples and comparative data, the composite solid fluorine flux of the present invention can effectively fix the corrosive fluorides produced by the combustion of high-fluorine fluorite, significantly improving the accuracy of measurement and the service life of the combustion tube.

[0042] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.

Claims

1. A composite solid fluorine co-solvent for determining the sulfur content in fluorite, characterized in that, By weight ratio: 50%–80% tungsten granules, 15%–30% tin granules, and 10%–25% composite solid fluorine oxidant; The composite solid fluorine oxidant comprises calcium carbonate, lanthanum oxide, and copper oxide in a weight ratio of (4.5–5.5):(2.5–3.5):(1.5–2.5).

2. The composite solid fluorine co-solvent for determining the sulfur content in fluorite according to claim 1, characterized in that, The particle size of calcium carbonate, lanthanum oxide, and copper oxide is no higher than 200 mesh.

3. The composite solid fluorine co-solvent for determining the sulfur content in fluorite according to claim 1, characterized in that, Tungsten granules 60%–70%, tin granules 16%–25%, composite solid fluorine oxidant 12%–22%.

4. The composite solid fluorine co-solvent for determining the sulfur content in fluorite according to claim 1, characterized in that, The weight ratio of calcium carbonate, lanthanum oxide and copper oxide is (4.8–5.2):(2.8–3.2):(1.8–2.2).

5. The composite solid fluorine co-solvent for determining the sulfur content in fluorite according to claim 1, characterized in that, The tungsten particles have a particle size of 0.4 mm to 0.8 mm and a purity of ≥99.9%; the tin particles have a particle size of 0.2 mm to 0.5 mm and a purity of ≥99.5%.

6. A method for preparing the composite solid fluorine co-solvent for determining the sulfur content in fluorite according to any one of claims 1 to 5, characterized in that, Calcium carbonate, lanthanum oxide, and copper oxide are mixed, ground, and passed through a 200-mesh sieve to obtain a composite solid fluorine oxidant powder. Then, tungsten granules and tin granules are added, mechanically mixed evenly, and dried at 105–120°C for 2–4 hours. After cooling, the mixture is sealed for later use.

7. A method for determining the sulfur content in fluorite, characterized in that, The fluorite sample to be tested is placed in a ceramic crucible, and the composite solid fluorine co-solvent for determining the sulfur content in fluorite as described in any one of claims 1 to 5 is added to cover the fluorite sample. A high-frequency infrared carbon-sulfur analyzer is turned on to perform combustion determination, and the sulfur content in fluorite is calculated.

8. The method for determining the sulfur content in fluorite according to claim 7, characterized in that, The mass of the composite solid fluorine co-solvent is 2 to 5 times the mass of the fluorite sample to be tested.

9. The method for determining the sulfur content in fluorite according to claim 7, characterized in that, The mass of the composite solid fluorine co-solvent is 3 to 4 times the mass of the fluorite sample to be tested.